An Evidence-Informed Theory of Change for Facilitating Disengagement from Violent Extremism: Insights from the Community Integration Support Program - Spaaij, Ramón (Journal for deradicalization, 2025)
This paper addresses a persistent issue in the literature on countering violent extremism (CVE): the lack of robust program theory and an accepted analytical framework for understanding change mechanisms and measuring outcomes. The absence of a comprehensive theory of change in CVE programming can hinder conceptual clarity and practical understanding of the intervention philosophy, weakening the basis for intended outcomes and underlying mechanisms of change. The authors present an evidence-informed theory of change for the Community Integration Support Program (CISP), the longest-running CVE program in Australia. This mixed methods research, which combines quantitative analysis of detailed client assessments and 52 semi-structured interviews with clients and other key stakeholders, examines the main program ingredients that enable the CISP to achieve its intended outcome of client disengagement from terrorism and violent extremism. The results provide novel insights into the change mechanisms of CVE interventions that aim to support disengagement from terrorism and violent extremism, highlighting the need for programs to be holistic, tailored to individual needs, and delivered in a culturally appropriate way by trusted and skilled staff. The findings also indicate that most clients do not show substantive positive change until three or more years in the program. The authors encourage CVE interventions to move beyond ill-defined or generic theories of change to ones that are evidence-based and context-specific. Acknowledgements This research was funded by Victoria Police and conducted in partnership with the Board of Imams Victoria (BOIV).